E-003 Evaluation of Strategies to Reduce Time to Revascularization in Acute Ischemic Stroke. (29th July 2016) - Doerr, A; Jenkins, S; Davis, J
Abstract : Background: Stroke is significant cause of morbidity, disability and mortality in the United States today. There is growing support for the need for process improvement, specifically, reducing time to reperfusion in endovascular stroke therapy (EVT) to improve functional outcomes. It is suggested that every 30 minutes delay in revascularization of acute ischemic stroke leads to a 10.6% decrease in the potential for a good functional outcome (Khatri et al., 2009). Purpose: To identify the impact on specific hospital based process improvement strategies in the acute ischemic stroke patient population undergoing endovascular therapy with specific intent to decrease median arrival to revascularization time, thus increasing the potential for good functional outcome. We seek to evaluate the efficacy of three hospital-based methods to improve time to revascularization in EVT for stroke: early notification, streamlined transport process and utilization of feedback tool. Methods: The project includes a pre and post intervention retrospective review of patient 18 years or older, admitted through the emergency department, with hospital admission between January 1, 2014 and December 31, 2015, who undergo EVT for treatment acute ischemic stroke. Primary outcome variable: time from arrival to revascularization (first pass) and secondary outcome variables: functional outcome analysis utilizing pre procedure, post procedure and discharge modified Rankin score (MRS) 30 and 90 day MRS. The data points will be collected using the Stroke Time PI project tool based on the America Heart Association's Get with the Guidelines-Stroke (GWTG). Results: A total of 17 consecutive ED arrival endovascular ischemic stroke patients were reviewed, pre PI (Group 1, n = 9) and post PI (Group 2, n = 8). The timeline breakdown from patient arrival to revascularization is shown in Table 1. Preliminary analysis of the primary outcome demonstrates significant improvement in door to revascularization between the pre and post PI groups, 2:56 and 2:14 (p < .05) respectively, a statistically significant 40 minute decrease in time to treatment. Conclusions: Despite the relatively small sample size for the study, this evaluation provides evidence based practice strategies which could be implemented at stroke centers to reduce door to revascularization time in EVT. These strategies are also theorized to positively impact stroke outcomes due to the improvement in treatment times and will be reported with the final study analysis. Disclosures: A. Doerr: None. S. Jenkins: None. J. Davis: None.